2023
DOI: 10.3389/fgene.2023.1170260
|View full text |Cite
|
Sign up to set email alerts
|

Computable structured aptamer for targeted treatment of ovarian cancer

Abstract: Nucleolin protein expression is higher on the ovarian cancer cell surface. AS1411, a DNA aptamer, can bind with nucleolin protein specifically. In this study, we developed HA and ST DNA tiles to assemble six AS1411 aptamers to deliver doxorubicin. In addition, to superior serum stability and drug loading, HA-6AS and ST-6AS outperformed TDN-AS in cellular uptake. HA-6AS and ST-6AS exhibited satisfactory targeted cytotoxicity and achieved resounding lysosomal escape. Moreover, when injected into nude mice subcut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
0
0
Order By: Relevance
“…HA-6AS-DOX and ST-6AS-DOX demonstrated rapid cytotoxicity specifically against OC cells while exhibiting low levels of cytotoxicity towards normal ovarian epithelial cells. Additionally, the study revealed contrasting internalization patterns between HA-6AS and ST-6AS; HA-6AS displayed a more active targeting mechanism, whereas ST-6AS exhibited a predominantly passive targeting mechanism [118].…”
Section: Nucleolinmentioning
confidence: 90%
“…HA-6AS-DOX and ST-6AS-DOX demonstrated rapid cytotoxicity specifically against OC cells while exhibiting low levels of cytotoxicity towards normal ovarian epithelial cells. Additionally, the study revealed contrasting internalization patterns between HA-6AS and ST-6AS; HA-6AS displayed a more active targeting mechanism, whereas ST-6AS exhibited a predominantly passive targeting mechanism [118].…”
Section: Nucleolinmentioning
confidence: 90%